LAPANGAN TEMBAK WASAKA DI BANJARMASIN - Maulida, Aulia Noor; Heldiansyah, JC (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
South Kalimantan for the past 10 years has shooting athletes that have the potential to compete national and international. But it is not balanced with facilities such as there is no shooting range that can accommodate all training activities of athletes. Training is the most important thing in achievement, but in fact, the current place for training does not support athletes to maximize their potential. Behavior architecture as a method to solve or maximize the potential of athletes starts with three parts of training: emotion, cognition, and performance. Wasaka Shooting Range designed to make athletes as main users have trained with metamorphosis concepts that prepare the athletes emotionally and cognitively. With this concept, the area is divided into three zones which is the transition, prepare, and main zone.